(untitled) (European Journal of Child Development, Education and Psychopathology, 2013)
Few investigations exist which have analyzed the effects that similar parenting behaviors have on adolescent psychological health outcomes across different nations. It is important to understand how common parenting behaviors may influence outcomes differently according to population setting. Italy and the Netherlands are two European countries that are dissimilar in family and societal norms and regulations. This study investigated the one year longitudinal associations of parental strictness of rules on adolescent psychological health indicators including: self-confidence, self-esteem, aggression, depression, positive self-perception, and sense of alienation. Additionally, we tested the potential moderating role that country, age and gender had on these associations. The sample consisted of 510 Italian and Dutch adolescents (mean age=17.4, SD=1.42). The sample was representative of adolescents attending high school in the selected parts of both countries. A general linear mixed model was applied to investigate main effect and moderating associations. Results showed that the effect of strictness of family rules on both self-confidence (?=-0.38, p=0.04) and positive self-perception (?=0.28, p=0.03) was lower among Dutch and older adolescents. Results point to the fact that greater efforts should be conducted which account for the influence of cultural and social effects of parenting on adolescent health outcomes.